COMPROMISING DILEMMA AS REFLCTED IN POEM â€œSTOPPING BY WOODS ON A SNOWY EVENINGâ€ BY ROBERT FROST - Zaman, Badrus (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2012)
Every human have problems in his/her life. Sometimes those are easy and difficult ones, then they feel confused to decide which one should they take because those are good for their future life. But willy-nilly, they have to choose one of them. The condition as experienced by Frost reflected in his poem entitled Stopping by Woods on a Snowy Evening, in which he experience difficult something in taking decision in other to make him into dilemma. Two problem formulations which were discussed in this final project are 1) What choices does Frost face as portrayed in Stopping by Woods on a Snowy Evening?, 2) How does Frost compromise with his dilemma as reflected in selected poem? In doing the analysis, the writer utilized structural and psychological approache. The type of this research are descriptive qualitative. So that it can support the analysis by making the description of the selected quotation, sentence, phrase, and narration that appropriate the statement problems. The results of the study are 1) Frost has two problems, namely, want to enjoy the beautiful scenery at the middle of the woods, and the duties and responsibility that he has to do in his life, 2)Â  After deep consideration about positive and negative effect in the future life. Finally, in compromising his dilemma he decides to give priority to do his duties and responsibilities and put aside his desire to keep enjoying the woods. The suggestion that could be submitted was every people certainly have ever experienced a dilemma in his/her life, and every decision that is taken has two sides in his/her life, they are positive and negative sides. So, you must think twice and consider it carefully before you are taking decision when you are facing by two options in your life. Besides, we should not be selfish or egoist person in the world because we cannot stand alone in the world, but in our life we always needs the other people helping in our life.